CLPP coordinates mitoribosomal assembly through the regulation of ERAL1 levels. (20th October 2016) - Szczepanowska, Karolina; Maiti, Priyanka; Kukat, Alexandra; Hofsetz, Eduard; Nolte, Hendrik; Senft, Katharina; Becker, Christina; Ruzzenente, Benedetta; Hornig‐Do, Hue‐Tran; Wibom, Rolf; Wiesner, Rudolf J; Krüger, Marcus; et al.
Abstract: Despite being one of the most studied proteases in bacteria, very little is known about the role of ClpXP in mitochondria. We now present evidence that mammalian CLPP has an essential role in determining the rate of mitochondrial protein synthesis by regulating the level of mitoribosome assembly. Through a proteomic approach and the use of a catalytically inactive CLPP, we produced the first comprehensive list of possible mammalian ClpXP substrates involved in the regulation of mitochondrial translation, oxidative phosphorylation, and a number of metabolic pathways. We further show that the defect in mitoribosomal assembly is a consequence of the accumulation of ERAL1, a putative 12S rRNA chaperone, and novel ClpXP substrate. The presented data suggest that the timely removal of ERAL1 from the small ribosomal subunit is essential for the efficient maturation of the mitoribosome and a normal rate of mitochondrial translation. Synopsis: A combination of proteomics and mouse knockout approaches identifies substrates of the mammalian ClpXP protease, showing that it controls mitochondrial homeostasis by ensuring assembly and function of mitochondrial ribosomes. Mammalian ClpXP substrates are involved in mitochondrial translation, oxidative phosphorylation, and metabolism. ClpXP determines the rate of mitochondrial protein synthesis by regulating the level of mitoribosome assembly. Timely removal of ERAL1 from the small ribosomal subunit is essential for the efficient maturation of the mitoribosome and a normal rate of mitochondrial translation. Abstract : A combination of proteomics and mouse knockout approaches identifies substrates of the mammalian ClpXP protease, showing that it controls mitochondrial homeostasis by ensuring assembly and function of mitochondrial ribosomes.